Genetic alterations related to endoscopic treatment of colorectal tumors. Issue 1 (25th June 2019) - Kuno, Toru; Tsukui, Yuya; Takano, Shinichi; Maekawa, Shinya; Yamaguchi, Tatsuya; Yoshida, Takashi; Kobayashi, Shoji; Iwamoto, Fumihiko; Ishida, Yasuaki; Kawakami, Satoshi; Tanaka, Keisuke; Fukasawa, Yoshimitsu; et al.
Abstract : Background and Aim: Genetic indicators of endoscopic resection for colorectal carcinoma remain inconclusive. This study analyzed genetic changes in early colorectal tumors that could inform decisions for endoscopic procedures. Methods: A total of 83 colorectal tumors from 81 patients, including adenoma ( n = 7), Tis–T1a ( n = 22), T1b ( n = 14), and advanced carcinoma ( n = 40), were analyzed. Tis tumors ( n = 16) and some T1 carcinomas ( n = 11) were analyzed as mixed adenomas and carcinomas. Lesions were laser‐capture microdissected for DNA extraction, and targeted sequencing of 50 cancer‐related genes was performed. Genetic data were then correlated with clinical records, including magnifying endoscopic findings. Results: Numbers of gene alteration rates in TP53 and SMAD4 increased with tumor progression from adenoma to carcinoma. Frequencies of mutant variants in TP53 ( P = 0.004) and rates of copy number loss in SMAD4 ( P = 0.006) increased in carcinoma components of mixed tumors compared to adenoma components. Moreover, adenoma components of T1b carcinomas had higher TP53 mutation rates than Tis or T1a carcinomas ( P = 0.011) and pure adenomas ( P = 0.026). Gene alterations in TP53 ( P = 0.0055) and SMAD4 ( P = 0.0055) increased in cases with irregular surface patterns of magnifying endoscopic findings. Conclusions: Numbers of copy number variations and TP53 and SMAD4 alterations were related to colorectal tumor progression. TP53 alteration rates in adenoma components were high in T1b carcinomas, warranting complete treatment with en bloc resection. Magnifying endoscopic findings might reflect the genetic status of colorectal tumors. Abstract : Despite recent large‐scale gene analyses, genetic indicators of endoscopic resection for colorectal carcinoma remain inconclusive. Next‐generation sequencing analyses of 83 colorectal tumors demonstrated that numbers of copy number variations and TP53 and SMAD4 alterations were related to colorectal tumor progression. Furthermore, TP53 alteration rates in adenoma components were high in T1b carcinomas, warranting complete treatment with en bloc resection.